Absence of an Oral Hearing in Administrative Disputes: - Mario Rašić (Central European Public Administration Review)
Purpose: The right to an oral hearing is an essential element of Article 6 of the Convention for the Protection of Human Rights and Fundamental Freedoms. This is particularly emphasised in administrative procedures where the parties are in a hierarchical relationship. The absence of an oral hearing can significantly limit a party’s right to a fair trial. Therefore, this paper aims to explore the positive law and state of play in the Republic of Slovenia and the Republic of Croatia regarding the right to an oral hearing. The purpose of this paper is to analyse relevant legislation and case law with the goal of proposing future legislation that better aligns with effective legal protection. Design/Methodology/Approach: Desk research was conducted to analyse current legal solutions and case law using sociological research methods. These involved analysing domestic and international legal texts and reviewing the rules governing national administrative procedures in the countries included in the research, as well as against decisions of the European Court of Human Rights. In addition, the research used a combination of primary and secondary data sources. Findings: Administrative courts should prioritise procedural justice and equality of arms, even when there is no clear need for oral hearings, especially if one of the parties requests to appear before the court. To minimise damaging discretion, both parties should consent to relinquishing the right to an oral hearing, which should be mandatory by default. Academic contribution to the field: The primary contribution of this paper lies in its de lege ferenda suggestions regarding the right to an oral hearing, which could potentially enhance the protection of human rights in relation to a fair trial in both administrative disputes and administrative procedures. Originality/Value: This research is original as it presents a comparative analysis of administrative procedure and disputes in selected Member States. To the best of the author’s knowledge, no such comparative study has been conducted before. The findings of this research could have significant value as they highlight the need for improving procedural justice and equality of arms in ensuring a fair trial in administrative disputes.